Estimating baseline water levels for mine closure - Jackson, T.R.; Zhan, G. (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Baseline hydrologic data, such as groundwater levels in wells, are required to understand mine-induced impacts to the environment, both during mining operations and closure. Baseline data have natural temporal variability; however, capturing the full range of variability in baseline data is challenging. Using long-term (1900–present) climatic data, a baseline water-level record can be constructed that provides an understanding of the expected range of natural temporal variability. This paper presents an analytical approach for constructing a theoretical long-term (1900–2023) water-level record, using the Turquoise Ridge Mine Complex in northern Nevada as an example. The approach relies on an underlying conceptual model of groundwater recharge and discharge. Recharge and discharge are assumed to be in a state of dynamic equilibrium, where water levels fluctuate over annual-to-decadal timescales but have a century-scale steady-state condition. The baseline water-level record compares favourably to measured water levels, thus successfully validating the approach.